Strategi Produksi Woodchip Secara Berkelanjutan di Pulau Jawa dalam Mendukung Diversifikasi Sumber Energi dan Transisi Energi - Imam Supriyadi; Suyono Thamrin; Rudy Laksmono; Sri Murtiana (PendIPA Journal of Science Education, 2026)
Indonesia’s energy security faces structural challenges due to the dominance of coal in the national energy mix, leading to sustainability risks and increased greenhouse gas emissions. To achieve the 23% renewable energy target by 2025, the government promotes biomass utilization through co-firing in coal-fired power plants. However, its implementation remains constrained by limited sustainable biomass supply and inefficient supply chain systems. This study aims to formulate an optimal allocation strategy for woodchip production in Java as a primary biomass source to support co-firing implementation. The methodology integrates spatial analysis using the Center of Gravity approach and SWOT analysis to develop an integrated development strategy. Key indicators include biomass availability, transportation accessibility, proximity to demand centers, and policy support. The results indicate that Java has a biomass residue potential of 143.58 million tons annually, yet faces a significant land gap of 189,849 hectares for energy plantations. Supply chain optimization reduces delivery time by up to 44% and logistics costs by 38%, with an optimal distribution radius of 80 km serving 16 coal-fired power plants with a total capacity of 14,645 MW. The proposed integrated strategy includes capacity expansion, land intensification, feedstock diversification, and supply chain efficiency through multi-stakeholder collaboration. Overall, the strategy ensures a sustainable biomass supply of 10.2 million tons by 2025 without additional deforestation. The integration of woodchip in co-firing contributes to a 15% reduction in CO₂ emissions and improved plant efficiency, thereby accelerating energy transition, strengthening energy security, and supporting Indonesia’s Net Zero Emission 2060 target.